Increasing Urban Heat Island area in Jakarta and it's relation to land use changes. Issue 1 (April 2021) - Putra, C D; Ramadhani, A; Fatimah, E
Abstract: Urban Heat Island (UHI) is a phenomenon that occurs in almost all metropolitan cities in the world. The UHI phenomenon also occurs in Jakarta, the capital city of Indonesia, a metropolitan city with an area of 662 km2, 12 million inhabitants, and an average population density of 16, 000 per km2. Previous research shows the area of UHI, areas with temperatures> 300, in Jakarta in 1989 reached 84.53 km2 or 0.1 % of the total area. Based on these facts, the aim of this study is to identify changes in the area of UHI areas from 2008 to 2018 and their relation to land use changes. Temperature data used in this study are from Landsat satellite images in 2008, 2013 and 2018, while the land use data used are from National Geospatial Information Agency. Similar to the previous research, the operational definition of UHI used in this study is that UHI is the area with surface temperature > 300. The method used is spatial analysis and comparison method. The results showed that the area of UHI in Jakarta had increased. The areas of UHI Jakarta were 36.5%, 84.7%, and 85.2% of the total areas respectively in 2008, 2013 and 2018. The increases of UHI's area were in line with the increases of the built areas that respectively 79.2%, 82.9% and 85.2%. Land use for housing, commercial and services, industry and warehousing and transportation facilities seem to be more significantly affecting the increases of UHI area rather other land uses.